التفكير خارج الصندوق وعلاقته بالتحصيل النوعي الدراسي في مادة الفيزياء لدى طلبة المرحلة الاعدادية (Journal of the College of Basic Education, 2025)
Recently, interest in mental processes, including thinking, has increased as a result of the massive scientific development of information, which called for care to know the way each individual thinks and how to deal with these developments. Surrounding thinking is one of the types of thinking that was associated with the scientist Edward De Bono. This term, which means research to solve problems in non- Traditional or clearly irrational, it means moving sideways from one idea to another in multiple ways as opposed to vertical thinking that relies on rigid sequences and sequential steps.And that the academic achievement of physics has a significant impact on directing students towards information and the extent to which they benefit from it. Hence, the problem of the current research is determined by answering the following question: Is there a relationship between perceptive thinking and academic achievement among middle school students?The current research was limited to fifth grade preparatory students for the morning study in its two branches (applied - biological) from (males - females) for the academic year (2021-2022).In order to verify the objectives of the current research, the researcher built a test for circumferential thinking according to the proposals, theories and opinions of De Bono in circumferential thinking, and the test consisted of (33) questions, and the researcher extracted the psychometric characteristics of the test; So, she relied on apparent validity, constructive validity, and reliability coefficient by means of re-testing, so the stability coefficient reached (0.70), and the reliability coefficient in the analysis of variance reached (0.70). From its validity, distinction, and effectiveness of its false alternatives, the researcher made sure of the stability of the test in two ways. The researcher reached the following results:Preparatory stage students have a good level of peripheral thinking.There are statistically significant differences among middle school students in peripheral thinking according to the variables of gender (male - female) in favor of females, and the branch (applied - biological) in favor of the applied branch.Preparatory stage students have a good level of academic achievement.There are statistically significant differences among middle school students inacademic achievement according to the variables of gender (male - female) in favor of females, and the (applied - biological) branch in favor of the biological branch.There is a statistically significant relationship between peripheral thinking and academic achievement in the research sample.There are no differences in the relationship between perceptive thinking and academic achievement according to the variables of gender and branch.Based on the results of the current research, the researcher recommended a number of recommendations and proposals